The Influence of Timeliness and Product Availability in Logistics Distribution on Partner Satisfaction at Perum BULOG in Bengkalis Regency - Triana Lorenza Munthe; Muhammad Arif; Supriati Supriati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to examine the simultaneous and partial influence of timeliness and product availability in logistics distribution on partner satisfaction at Perum Bulog in Bengkalis Regency. This study employed a quantitative approach using an associative research design. The population consisted of partners of Perum Bulog in Bengkalis Regency. The sample was determined using a saturated sampling technique. Data were collected through a structured questionnaire and analyzed using multiple linear regression analysis. The results indicate that timeliness and product availability simultaneously have a positive and significant influence on partner satisfaction. Partially, timeliness has a positive and significant influence on partner satisfaction. Likewise, product availability also has a positive and significant influence on partner satisfaction. These findings imply that improving delivery timeliness and maintaining product availability are essential for enhancing partner satisfaction and strengthening the effectiveness of logistics distribution at Perum BULOG in Bengkalis Regency.